PEMANFAATAN SUMBER DAN MEDIA PEMBELAJARAN DALAM MENUMBUHKAN BERPIKIR KREATIF PADA ANAK USIA DINI KELOMPOK B DI TK MUSLIMAT NU 2 SINGOSARI MALANG - Nur Lailatul Maghfiroh; Mohammad Afifulloh; Mutiara Sari Dewi (UNISMA, 2022)
The teacher is a teaching component that plays an important role in the success of the learning process. Learning is a process of interaction between students and educators and learning resources in a learning environment. So the teacher is an important factor in preparing learning resources. Muslimat NU 2 Kindergarten has media and game resources that can increase the motivation to think creatively for early childhood. This type of research is aqualitative research with a case study approach with research subjects of group B children. The results of the research on learning resources and media to foster creative thinking are planned learning tools, varied learning resources and media and increased child development assessment results